1999
DOI: 10.1038/sj.leu.2401303
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of p16ink4a is associated with a poor prognosis in childhood acute lymphoblastic leukemia

Abstract: The tumor suppressor gene p16 ink4a is homozygously deleted in numerous T as well as in some B lineage acute lymphoblastic leukemia (ALL). We therefore analyzed the clinical and biological implications of this feature by studying p16 ink4a expression in 58 cases of childhood ALL. mRNA and protein were significantly correlated and both appeared more highly expressed in B than in T lineage ALLs: 13 out of the 15 T cell ALLs did not show any p16 ink4a expression. The main result of this study is the strong progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…This is unexpected as one might predict that reduced levels of p16 would result in deregulated activation of cyclindependent kinase 4/6 resulting in uncontrolled cell-cycle transition through the Rb pathway, leading to a higher tumour growth rate. However, high levels of p16 mRNA expression have been related to a shorter event-free survival in acute lymphoid leukaemia (Mekki et al, 1999), breast cancer (Hui et al, 2000) and neuroblastoma (Omura-Minamisawa et al, 2001), and loss of p16 protein expression has previously been associated with the presence of metastatic disease at diagnosis in primary ESFT (P ¼ 0.026, n ¼ 20; Maitra et al, 2001). Interestingly, we found no correlation between p16 protein expression and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This is unexpected as one might predict that reduced levels of p16 would result in deregulated activation of cyclindependent kinase 4/6 resulting in uncontrolled cell-cycle transition through the Rb pathway, leading to a higher tumour growth rate. However, high levels of p16 mRNA expression have been related to a shorter event-free survival in acute lymphoid leukaemia (Mekki et al, 1999), breast cancer (Hui et al, 2000) and neuroblastoma (Omura-Minamisawa et al, 2001), and loss of p16 protein expression has previously been associated with the presence of metastatic disease at diagnosis in primary ESFT (P ¼ 0.026, n ¼ 20; Maitra et al, 2001). Interestingly, we found no correlation between p16 protein expression and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,4,6,11,12 Flow cytometry is an extremely sensitive technique, but the need for prior permeabilization to study p16 INK4a can induce substantial morphological changes in leukemic blasts. Immunocytochemistry technique allows direct identification of leukemic cells leading to easier interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been also reported that enhanced expression of p16 INK4a gene was associated with poor prognosis in childhood ALL. 3 The high level of p16 INK4a expression group was associated with high proliferation rate and enhanced cellular survival. We also observed in our study, in some patients with unfavorable karyotype, a high proportion of leukemic cells expressing the p16 INK4a protein, but the difference was not statistically significant.…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…Par ailleurs, le promoteur et l'exon 1 de INK4a présentent un îlot CpG [6] qui recouvre un certain nombre de ces sites consensus ( Figure 1B) ; sa méthy-lation, anormale, induit l'extinction du gène. Bien qu'une régulation post-transcriptionnelle de INK4a ait été décrite [20], l'analyse conjointe de l'ARNm et de la protéine montre que c'est essentiellement au niveau transcriptionnel qu'intervient sa régulation [11,12,21] : l'étude de la transcription d'INK4a devrait donc permettre de déterminer les facteurs impliqués dans sa régulation, et donc dans la sénescence cellulaire, facteurs dont le dérèglement serait à l'origine du développement de tumeurs.…”
Section: Protéine Bhlh E47unclassified